Optimization of Analog Meat Formula Made from "Gepak Kuning" Soybean Flour, Carrageenan, and Pectin Using the Mixture Design Method - Azkiyah, Lailatul; Puji Lestari, Ning; Indarto; Giyarto; Alfi Ngizati, Naila (Jurnal Agrinika: Jurnal Agroteknologi dan Agribisnis, 2025)
The development of analog meat products signifies a significant progression in plant-based food innovation, aiming to replicate conventional meats' nutritional and sensory characteristics, such as beef, goat, and chicken. This study specifically examined the process of producing analog meat using soy flour as the main protein source, with carrageenan and pectin serving as the key dietary fiber and texturizing agents. Employing Design Expert 11.0.0 for Mixture Design, we prioritized parameters such as dietary fiber, protein content, and organoleptic qualities. The optimal formulation consisted of 44.42% soy flour, 16.2% carrageenan, and 9.38% pectin. This formulation produced an analog meat product with a protein content of 18.13% and dietary fiber levels of 23.19%, aligning with industry standards for plant-based alternatives. Sensory evaluation results, with an average acceptance score of 5.3 out of 7, indicate strong consumer appeal. These findings demonstrate the practical viability of this composition for commercial plant-based meat production, offering a nutritious and sustainable alternative to traditional meat. The study provided valuable insights for food manufacturers seeking to develop high-fiber. These protein-rich analog meat products cater to the increasing demand for healthier and environmentally friendly food options.